Upaya Guru dalam Meningkatkan Minat Membaca Siswa Kelas Dasar - Anjas Luchiyanti; Vanda Rezania (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
This study aims to determine how the teacher's efforts increased the reading interest of class III B students at SDN Kejapanan 4. There is still a problem in the learning process in class III B SDN Kejapanan 4 due to the lack of books, and library function could be more optimal, affecting student learning outcomes. Therefore, to overcome these problems, various efforts of teachers in the classroom when teaching are needed so that there is an increase in reading, namely through providing motivation or encouragement, providing more books and various types in the classroom reading corner, and habituation of literacy 15 minutes before learning begins. This research is descriptive qualitative research through documentation, observation, and interview with a teacher of IIIB SDN Kejapanan 4. The results showed that there still needed to be more student interest in reading activities. This can be seen when observing students play more fun during breaks than reading and the lack of students reading repeatedly; students only read occasionally and then close the reading book again.